Antibacterial Properties and Mechanism of Lysozyme-Modified ZnO Nanoparticles - Yuan, Kangrui; Liu, Xiaoliu; Shi, Jianxin; Liu, Wei; Liu, Kun; Lu, Hongmei; Wu, Dudu; Chen, Zhi; Lu, Chengyu (Frontiers in Chemistry, 2021)
The lysozyme-modified nanoparticles (LY@ZnO NPs) were synthesized via the reduction–oxidation method, and the morphology and structure of LY@ZnO were analyzed by Fourier transform infrared (FTIR), powder X-ray diffraction (XRD), scanning electron microscope (SEM) and particle size analysis. The antibacterial effects of LY@ZnO against Escherichia coli (E. coli, gram-positive bacteria) and Staphylococcus aureus (S. aureus, gram-negative bacteria) were discussed by measuring the zone of inhibition (ZOI) and growth inhibition. The antimicrobial experiments showed that LY@ZnO NPs possessed better antibacterial activity compared with the ZnO. Besides, the antibacterial mechanism of LY@ZnO was also investigated, which was attributed to the generation of reactive oxygen species (ROS). Furthermore, the toxicities of LY@ZnO in vivo and vitro were discussed by cell counting kit-8 method and animal experiments, showing the LY@ZnO possessed excellent biocompatibility. Finally, the therapeutic effect of LY@ZnO to rat skin infection model caused by methicillin-resistant Staphylococcus aureus (MRSA) was also studied, which exhibited good anti-infective activity. Our findings showed that LY@ZnO possessed tremendous prospects for microbial infection in patients, which would be helpful for a better understanding of enzyme-modified nanomaterials against bacteria.